Age estimation using Orthopantomograph and Willems method in Chitwan population: an original study - Kapoor, Deepika (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background: Utilization of age estimation has increased manifold in recent years. Various methods available for age estimation before the complete dentition has erupted and matured till the root closure stage include Nolla’s stages, Demirijan”s method, modified Demirijan’s method by Willems, Haavikko’s method. So, in this study we have tested that on Chitwan population of Nepal. Materials and methods: 60 patients between the ages 6-16 were selected and digital orthopantomographs of each of the patients was taken and then Demerijian method was applied and age estimation done by Willems method. Whereas the chronolical age was known and the reliability of this method on this population checked. Results: The study shows correlation between chronological age CA and estimated dental age DA in males - .965 while in females - .861 and it is statistically significant Conclusion: There was an underestimation of age i.e. the dental age was found out to be less than the actual chronological age of the sample. This shows the dental growth lag in the Chitwan population. It was also found that when a comparison is done between the males and females it is found out that the females mature earlier than the males.